NAVIGATING CHALLENGES: A SURVEY OF NON-SCIENCE STUDENTS’ EXPECTATIONS IN BASIC PHYSICS CLASSROOM - Chummongkol, Pathompong; Suttiwan, Witsanu; Tonsinon, Kanisorn; Butrattana, Chanita (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study investigated the expectations and challenges of 18 non-science track students regarding introductory physics courses at the upper secondary level in Thai schools. We employed a survey research design using a validated questionnaire to gather descriptive data. A panel of three experts validated the questionnaire. Data analysis was performed using descriptive statistics. The main findings revealed that most students (72.22%) found physics “enjoyable but sometimes not understanding,” and mathematical calculations were the most significant challenge (66.67%). Students highly preferred learning support in the form of clear explanations (M=4.11, SD=0.96) and step-by-step problem-solving (M=4.06, SD=0.87). This research is unique in its focused examination of physics learning expectations among non-science track students within the Thai educational context, an area that has been understudied. The findings contribute to the field by providing specific insights into the challenges and support needs of this distinct student population. The results suggest that physics instruction for non-science students should incorporate differentiated teaching strategies, focusing on clear, step-by-step problem-solving and real-world applications to enhance conceptual understanding and engagement. This study’s findings can serve as a valuable guideline for designing future physics curricula and professional development programs for teachers of non-science track students.